2019
DOI: 10.3847/2041-8213/ab1141
|View full text |Cite
|
Sign up to set email alerts
|

First M87 Event Horizon Telescope Results. VI. The Shadow and Mass of the Central Black Hole

Abstract: We present measurements of the properties of the central radio source in M87 using Event Horizon Telescope data obtained during the 2017 campaign. We develop and fit geometric crescent models (asymmetric rings with interior brightness depressions) using two independent sampling algorithms that consider distinct representations of the visibility data. We show that the crescent family of models is statistically preferred over other comparably complex geometric models that we explore. We calibrate the geometric m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
527
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,182 publications
(548 citation statements)
references
References 99 publications
18
527
1
2
Order By: Relevance
“…In a given simulation, we find that there is no clear convergence of d log ρ /d log r to a particular value in the steady state flow exterior to the inner 10-30 GM/c 2 , as might be expected if there were a unique self-similar solution for the structure of RIAFs. By contrast, such a well-defined radial profile is seen in hydrodynamic α models of RIAFs (e.g., Stone et al 1999;Yuan et al 2012). It is unclear if this difference between the hydrodynamic and MHD models reflects the very different angular momentum and energy transport physics in the two different simulations or if our simulations still do not have sufficient dynamic range to reach a quasi self-similar state.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In a given simulation, we find that there is no clear convergence of d log ρ /d log r to a particular value in the steady state flow exterior to the inner 10-30 GM/c 2 , as might be expected if there were a unique self-similar solution for the structure of RIAFs. By contrast, such a well-defined radial profile is seen in hydrodynamic α models of RIAFs (e.g., Stone et al 1999;Yuan et al 2012). It is unclear if this difference between the hydrodynamic and MHD models reflects the very different angular momentum and energy transport physics in the two different simulations or if our simulations still do not have sufficient dynamic range to reach a quasi self-similar state.…”
Section: Resultsmentioning
confidence: 69%
“…Stone et al (1999),, andYuan et al (2012) studied the radial structure of RIAFs using axisymmetric hydrodynamic simulations with an α viscosity, with outcomes differing with the details of that viscosity. The differences between hydrodynamic and magnetohydrodynamic (MHD) simulations make it difficult to know how to connect the results of those simulations to the MHD problem considered here.…”
mentioning
confidence: 99%
“…Recently, the EHT Collaboration announced their first image concerning the detection of an event horizon of a supermassive black hole at the center of a neighboring elliptical M87* galaxy [1][2][3][4][5][6]. With this image, it was found that the diameter of the center black hole shadow is (42 ± 3) µas with a deviation 10% from circularity, which leads to a measurement of the center mass, M = (6.5 ± 0.7) × 10 9 M [1].…”
Section: Introductionmentioning
confidence: 99%
“…The calculations of the shadow size and shape, and their observational implications from different black hole spacetimes or spacetimes of compact objects with exotic matters ether in general relativity or in modified theories of gravity have been extensively studied, see, for example, . Recently, the first observational data of the shadow image captured by EHT [1][2][3][4][5][6] have been used for constraining the black hole parameters and deviations from the Kerr metric [49][50][51][52][53]. Although these constraints are still not stringent enough, these works do show that the observational data does have the capacity for constraining black hole parameters beyond those presented in GR.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various kinds of astronomical observations strongly reveal that black holes do exist in our universe. The evidences so far are not limited to gravitational wave detection by LIGO and Virgo, but also include the images of black holes by Event Horzion Tecescope (EHT) [1][2][3][4][5][6]. However, compared to the precision of LIGO and Virgo, the pictures of black holes captured by EHT are not clear enough.…”
Section: Introductionmentioning
confidence: 99%